Minimizing distribution circuit loss by phase balancing using genetic algorithm - Reyes, Jose S. (2006)
Reduction of circuit loss has been a major concern of electric utilities. One aspect in distribution operations affection circuit loss is unbalanced loading or phase imbalance brought about by single-phase loads, two-phased loads, unbalanced three-phase loads, and unbalanced impedances. On the other hand, other concerns relating to an unbalanced system are system capacity problem, low voltage drop and nuisance tripping of ground protection relays. This paper describes a method of phase balancing of single and two-phase loads and laterals among the three-phase lines, of a three-phase unbalanced radial distribution system. The objective is to attain the global minimum of circuit loss in the primary lines. Power flow using backward-forward sweep algorithm for radial distribution systems was implemented to compute for the power loss. Genetic algorithm (GA) was used to propose loads and lateral phasing, instead of a large-scale combinatorial process. It was concluded that genetic algorithm can be implemented to propose phasing of single and two-phase loads and laterals among the three-phase lines to yield the global minimum loss.